التنبؤ بالولادة المبكرة بقياس تبدلات عنق الرحم بواسطة الأمواج ما فوق الصوتية - جراد, الهام يوسف (Latakia University Journal -Medical Sciences Series, 2016)
The study is carried on 65 pregnant patients attending the outpatient clinics and inpatient department of Obstetrics and Gynecology of Al Assad University Hospital from February- 2013 until February- 2014. They were divided to three groups. The first is preterm labor with intact membranes (25 patients). The second is PROM (20 patients). The third one is control group (20 patients). All of them were submitted to ultrasonography to find cervical changes (cervical canal length and diameter of internal os in order to predict preterm delivery. Cervical canal length has a sensitivity of 91.43%, a specificity of 100%, a positive predictive value of 100%, a negative predictive value of 76.92%, and a relative risk (95% CI) of 4.33 (1.61-11.69) among patients with short cervical canal length and those with normal cervix.Diameter of internal os as a predictor of preterm delivery has a sensitivity of 60%, a specificity of 60%, a positive predictive value of 84%, a negative predictive value of 30%, and a relative risk (95% CI) of 1.2 (0.86–1.68)تم إجراء الدراسة على65 سيدة من النساء الحوامل المترددات على العيادات الخارجية والداخلية في قسم النساء والتوليد في مستشفى الأسدالجامعي خلال الفترة الممتدة من شباط 2013 حتى شباط 2014. و تم تقسيمهم الى ثلاث مجموعات الأولى خمس و عشرون مريضة لديهن مخاض باكر مع أغشية سالمة والثانية عشرون مريضة لديهن انبثاق اغشية باكر، والمجموعة الثالثة عشرون مريضة للمقارنة.كل المريضات سوف تخضعن للكشف بالموجات ما فوق الصوتية لتقييم التغيرات الطارئة على عنق الرحم (طول عنق الرحم وقطر الفوهة الباطنة) بغرض التنبؤ بالولادة المبكرةان طول عنق الرحم كمشعر للتنبؤ بالولادة المبكرة ذو حساسية عالية وصلت حتى 91.43% و ذو نوعية أعلى وصلت حتى 100% وذو قيمة تنبؤية موجبة عالية وصلت حتى 100% و ذو قيمة تنبؤية سلبية 76.92%.إن خطر الولادة في المريضات اللواتي لديهن عنق رحم قصير( اقل أو يساوي 25 مم) هو 4.33 ضعف أولئك اللواتي لديهن عنق رحم طبيعي ( اكثر من 25 مم).إن قطر الفوهة الباطنة لعنق الرحم كمشعر للتنبؤ بالولادة المبكرة ذو حساسية وصلت حتى 60% و ذو نوعية وصلت حتى 60% وذو قيمة تنبئية موجبة وصلت حتى 84% و ذو قيمة تنبئية سلبية وصلت حتى 30%.